2019
DOI: 10.1177/2047487318821772
|View full text |Cite
|
Sign up to set email alerts
|

Prevention: From the cradle to the grave and beyond

Abstract: Present cardiac prevention mainly focuses on risk reduction later in life, and focuses also mainly on reducing risk factors for coronary heart disease. However, multiple studies have gathered evidence that the development risk of cardiovascular disease starts early in life and that even preconceptional influences play an important role in lifetime risk. Therefore, the importance of well-timed prevention strategies to reduce cardiovascular disease is well established. In this article, we discuss different risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
0
7
0
13
Order By: Relevance
“…[33][34][35][36][37] A stepwise strategy is recommended: follow-up, referral to special multidisciplinary programmes and pharmacotherapy. 6 Numerous technologies are available to provide remote smoking cessation guidance such as telephone counselling, video consultation, internet-based interventions, text messaging or mobile applications. An extensive meta-analysis researching the effect of telephone counselling for smoking cessation was conducted in 2019.…”
Section: Remote Smoking Cessationmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36][37] A stepwise strategy is recommended: follow-up, referral to special multidisciplinary programmes and pharmacotherapy. 6 Numerous technologies are available to provide remote smoking cessation guidance such as telephone counselling, video consultation, internet-based interventions, text messaging or mobile applications. An extensive meta-analysis researching the effect of telephone counselling for smoking cessation was conducted in 2019.…”
Section: Remote Smoking Cessationmentioning
confidence: 99%
“…5 Therefore, there is need for optimal lifelong secondary prevention. 6 Secondary prevention for CVD consists of three pillars: guideline-directed medical therapy (GDMT), adopting a healthy lifestyle, and patient education to increase health literacy. [5][6][7][8][9] The goal of GDMT is prescribed, either to obtain clinically stabilisation of patients or to add preventive medications to secondary prevention strategies.…”
mentioning
confidence: 99%
“…Концепция профилактики ССЗ на протяжении всей жизни В последние годы развивается новая концепция профилактики ССЗ, заключающаяся в их профилактике на протяжении всей жизни [7]. Одной из предпосылок такого подхода стало изучение воздействия, помимо основных "классических" ФР ССЗ (курение, повышенное артериальное давление, гиперлипидемия и др.…”
Section: Introductionunclassified
“…Несмотря на то, что роль воздействий уже на самых ранних этапах жизни, и даже до зачатия, хорошо доказана, большая часть публикаций и рекомендаций сконцентрирована на профилактических вмешательствах в более поздние периоды жизни. При этом важное значение имеет организация своевременных превентивных мер, начиная с самых ранних этапов жизни [6,7,16]. В данной статье рассмотрены профилактические мероприятия на этапе формирования организма: преконцепционный, пренaтальный и грудной периоды.…”
Section: Introductionunclassified
“…Recently, a review discussed cardiovascular risk factors which should be noted from the preconceptional phase to the last frail stages of life, and suggested that healthy lifestyle habits should be initiated from infancy and maintained during the whole lifetime to avoid SCD. 4 Achieving more ideal CVH metrics is associated with a lower risk of incident cardiovascular disease, stroke, and other related metabolic diseases, such as hypertension and type 2 diabetes. [5][6][7] However, the association of ideal CVH from early life and SCD is still not fully assessed.…”
mentioning
confidence: 99%